Prevalence of inflammatory bowel disease in patients with airways disease. - Raj, A; Birring, S; Green, R; Grant, A; de Caestecker, J; Pavord, I (2008)
BACKGROUND: Case reports and case series have suggested an association between inflammatory bowel disease (IBD) and airways disease, but there are no data demonstrating a higher prevalence of IBD among patients with airways disease. Furthermore, no consistent radiological, pulmonary or pathological abnormalities have been demonstrated in patients with both conditions. AIMS: To determine the prevalence of IBD among patients with airways disease and to evaluate clinical and pathophysiological features. METHODS: A retrospective analysis of outpatients with airways disease over a 10-year period. RESULTS: IBD was four times more prevalent among patients with airways disease compared with published local IBD prevalence [Odds Ratio 4.26, 95% CI 1.48, 11.71, p=0.006; Crohn's disease OR 5.96, 95% CI 1.94, 18.31, p=0.002 and ulcerative colitis OR 4.21, 95% CI 1.71, 10.41, p=0.001]. IBD was more frequent in all types of airways disease except asthma; the association was particularly strong for conditions associated with productive cough. All except 1 patient had established IBD before the onset of respiratory symptoms. There were no obvious radiological differences between ulcerative colitis and Crohn's disease cases. There was a trend for a higher lymphocyte count (despite a tendency to lower blood lymphocyte count) but lower sputum neutrophil count in patients with Crohn's disease compared with ulcerative colitis. There were no significant differences in physiological measurements of pulmonary function between the two types of IBD. CONCLUSION: Our findings support an association between airways disease and inflammatory bowel disease, particularly non-asthmatic airways disease with productive cough.